1994
DOI: 10.2307/1511128
|View full text |Cite
|
Sign up to set email alerts
|

Social-Emotional Development of Students with Learning Disabilities

Abstract: This article presents a model of development for children and youth with disabilities. The model incorporates 14 variables in three domains that have not been fully delineated by the field, including emotional, social, and behavioral development. In general, much more research, particularly intervention research, is needed in each of the 14 areas. Also, the data from several of the areas indicate that development may be more seriously hampered with increasing age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
81
0
10

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 154 publications
0
81
0
10
Order By: Relevance
“…Chapman and Prochnow (2000), showed that failure of students with dyslexia leads them to be less motivated in reading tasks. Bender and Wall (1994), reported that elementary students with learning disability have lower motivation. Additionally, Burden and Burdett (2005), findings revealed that the experience of dyslexia may lead to a major challenge to the self-esteem of some students with dyslexia or even to a negative impact upon their general self-development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chapman and Prochnow (2000), showed that failure of students with dyslexia leads them to be less motivated in reading tasks. Bender and Wall (1994), reported that elementary students with learning disability have lower motivation. Additionally, Burden and Burdett (2005), findings revealed that the experience of dyslexia may lead to a major challenge to the self-esteem of some students with dyslexia or even to a negative impact upon their general self-development.…”
Section: Discussionmentioning
confidence: 99%
“…Students with dyslexia may appear to be unmotivated; however, their lack of motivation may actually result from chronic academic failure (McGrady, Lerner, & Boscardin, 2001). Bender and Wall (1994) reported that elementary students with learning disability have lower motivation than their peers without disability, given the repeated academic failure that many students with learning disability experience. Therefore, it is not surprising that these students with dyslexia are less motivated.…”
Section: Introductionmentioning
confidence: 99%
“…Autonomy support led to intrinsic motivation and positive attitudes towards science. The deprivation of psychological needs, however, has been reported to lead to unfortunate consequences such as dropout (Eisenman 2007;Hardre and Reeve 2003) and, in extreme cases, criminality (Quinn et al 2005;Winters 1997) or even suicidal behaviour (Bender and Wall 1994;Svetaz et al 2000).…”
Section: Motivation Through the Lens Of Self-determined Learningmentioning
confidence: 99%
“…Within integrated classrooms, students with special needs are more likely to be nominated by their nondisabled peers for aggressiveness and disruptiveness, and they are also more likely to be rejected by their schoolmates (Farmer, 2000;Farmer & Hollowell, 1994). Studies have also shown that students with learning disabilities are at a greater risk for depression and suicide (Bender, Rosenkrans, & Crane, 1999;Bender & Wall, 1994;Huntington & Bender, 1993;McBride & Seigel, 1997).…”
mentioning
confidence: 99%